2007
DOI: 10.1111/j.1467-9280.2007.01917.x
|View full text |Cite
|
Sign up to set email alerts
|

The Constructive, Destructive, and Reconstructive Power of Social Norms

Abstract: ABSTRACT-Despite a long tradition of effectiveness in laboratory tests

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

82
2,241
20
49

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 2,888 publications
(2,392 citation statements)
references
References 26 publications
82
2,241
20
49
Order By: Relevance
“…Finally, there are experimental studies that have demonstrated powerful effects of normsbased interventions in changing adults' behavior [118,119]. Doping researchers could utilize these findings and develop norms-based interventions to reduce the risk for doping use.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Finally, there are experimental studies that have demonstrated powerful effects of normsbased interventions in changing adults' behavior [118,119]. Doping researchers could utilize these findings and develop norms-based interventions to reduce the risk for doping use.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…The remaining 101 (66 female) participants (n = 29 in Condition 1, n = 27 in Condition 2, n = 23 in Condition 3, n = 22 in Condition 4; see Table 1 for sample characteristics) were sent four weekly email messages that started with the words: "Before taking part in this study you were drinking more alcohol than is recommended by health experts" (social norm messages that do not convey disapproval of unhealthy behaviors can inadvertently encourage them; Schultz et al, 2007). This preceded a message framed in one of four ways according to experimental condition (see Table 2); those in Condition 1 (Absolute only) were sent messages that simply stated the official guidelines for alcohol consumption; those in Chi-squared and orthogonal regression tests were used to test for differences in seeking of alcohol related information between conditions.…”
mentioning
confidence: 99%
“…One recent study conducted by the American Society for Microbiology (2010) used both telephone surveys (N = 3020) and observations of behaviors (N = 6028) and found that women are more likely to report and practice hand hygiene than man, regardless of what activity they just did. Other studies have discovered that women report hand hygiene intention and behavior more frequently than men due to greater acceptance of, and pressure from, social norms (Nichols, 2014;Schultz et al, 2007). Similar studies conducted among college students have reported similar findings (Taylor, Basco, Zaied, & Ward, 2010;White et al, 2005).…”
Section: Demographic Factorsmentioning
confidence: 68%
“…Perceptions about what important people think a person should do (Schultz, Nolan, Cialdini, Goldstein, & Griskevicius, 2007).…”
Section: Injunctive Normsmentioning
confidence: 99%